Hydrogen sulfide anion regulates redox signaling via electrophile sulfhydration - Nishida, Motohiro (2012)
An emerging aspect of redox signaling is the pathway mediated by electrophilic byproducts, such as nitrated cyclic nucleotide (for example, 8-nitroguanosine 3′,5′-cyclic monophosphate (8-nitro-cGMP)) and nitro or keto derivatives of unsaturated fatty acids, generated via reactions of inflammation-related enzymes, reactive oxygen species, nitric oxide and secondary products. Here we report that enzymatically generated hydrogen sulfide anion (HS(−)) regulates the metabolism and signaling actions of various electrophiles. HS(−) reacts with electrophiles, best represented by 8-nitro-cGMP, via direct sulfhydration and modulates cellular redox signaling. The relevance of this reaction is reinforced by the significant 8-nitro-cGMP formation in mouse cardiac tissue after myocardial infarction that is modulated by alterations in HS(−) biosynthesis. Cardiac HS(−), in turn, suppresses electrophile-mediated H-Ras activation and cardiac cell senescence, contributing to the beneficial effects of HS(−) on myocardial infarction–associated heart failure. Thus, this study reveals HS(−)-induced electrophile sulfhydration as a unique mechanism for regulating electrophile-mediated redox signaling.